Plan de negocios para la creación de panadería y pastelería en el municipio de San Sebastian en el corregimiento de San Valentín en el departamento del Magdalena (2022)
In the present study of this project, it refers to the realization of a business plan for the creation and commercialization of bakery and pastry products, located in the municipality of San Sebastián in the district of San Valentín, in a rural area, this due to the lack of a bakery in said corregimiento, in order to satisfy the needs of the inhabitants of San Valentín and corregimientos, villages, farms and all the neighboring towns, seeing that these sectors do not have a bakery that can offer them said products, and Thus, later on, position the company in neighboring municipalities and throughout the department. The business consists of the elaboration of bakery and confectionery products, the different types of bread that are most in demand in the population will be studied in detail in order to carry out the production and commercialization of these. The purpose of this business is to be able to satisfy the need that has been seen in this corregimiento of having a good high-quality product in a close way and accompanied by a good service.